Impact of mindfulness-based interventions on sports performance and mental health: An umbrella review - Boyuan Xie; Siman Lei; Ngai Choi; Siu Ming Choi; Xiuqiang Wang; Yiwen Chen (Journal of Exercise Science & Fitness, 2025)
Background/Objective: While Mindfulness-Based Interventions (MBIs) are increasingly explored for enhancing sports performance and mental health in athletes, existing systematic reviews present conflicting results regarding their efficacy due to methodological inconsistencies and varied athlete populations. To address these discrepancies, this umbrella review critically evaluates evidence from systematic reviews to determine the aggregate effects of MBIs on sports performance, mindfulness indicators, and mental health outcomes among athletes. Methods: Systematic searches of PubMed, Web of Science, PsycINFO, ScienceDirect, and Scopus were conducted from inception to January 2024. Included studies were systematic reviews examining MBIs for athletic populations and reporting on sports performance, mindfulness indicators, or mental health outcomes. Methodological quality of included reviews was appraised using AMSTAR-2. Results: Fifteen systematic reviews and meta-analyses, encompassing 10,503 athletes, met inclusion criteria. Most reviews indicated positive trends for MBIs in improving sports performance, mindfulness indicators and various mental health outcomes. However, substantial methodological heterogeneity in primary study designs and MBIs protocols across reviews limited definitive conclusions. Critically, AMSTAR-2 assessments revealed that the majority (11 of 15, 73 %) of included reviews were of critically low methodological quality, with the remainder rated as low quality. Conclusion: While MBIs show potential to foster improved sports performance and mental health in athletes, the current evidence base is considerably weakened by the poor methodological quality of existing systematic reviews. A pressing need exists for future research to employ more rigorous methodologies, standardised intervention protocols, and consistent outcome reporting to establish a robust evidence base for the application of MBIs in sports.